Assessing spectral and temporal processing in children and adults using temporal modulation transfer function (TMTF), Iterated Ripple Noise (IRN) perception, and spectral ripple discrimination (SRD) - Peter, Varghese; Wong, Kogo; Narne, Vijaya Kumar; Sharma, Mridula; Purdy, Suzanne C; McMahon, Catherine (Journal of the American Academy of Audiology, 2014)
There are many clinically available tests for the assessment of auditory processing skills in children and adults. However, there is limited data available on the maturational effects on the performance on these tests. The current study investigated maturational effects on auditory processing abilities using three psychophysical measures: temporal modulation transfer function (TMTF), iterated ripple noise (IRN) perception, and spectral ripple discrimination (SRD). A cross-sectional study. Three groups of subjects were tested: 10 adults (18-30 yr), 10 older children (12-18 yr), and 10 young children (8-11 yr) Temporal envelope processing was measured by obtaining thresholds for amplitude modulation detection as a function of modulation frequency (TMTF; 4, 8, 16, 32, 64, and 128 Hz). Temporal fine structure processing was measured using IRN, and spectral processing was measured using SRD. The results showed that young children had significantly higher modulation thresholds at 4 Hz (TMTF) compared to the other two groups and poorer SRD scores compared to adults. The results on IRN did not differ across groups. The results suggest that different aspects of auditory processing mature at different age periods and these maturational effects need to be considered while assessing auditory processing in children.